THE SENSITIVITY OF MANGROVE Rhizophora sp. STEM SKIN EXTRACT ON Aeromonas salmonicida - Jampil, Tirta Herlis; Syawal, Henni; Riauwaty, Morina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in July 2016 to Januari 2017 in the Laboratory of Parasites and Fish Disease of Fisheries and marine science University of Riau, Integrated Chemical Laboratory the Faculty of Mathematics and Natural Science of Health Muhammadyah University of Riau and Fish Quarantine Station, Quality Control and Safety of Fishery Products clas I Pekanbaru. The purpose of this study was to sensitivity determine the ability of Rhizophora sp. stem skin extracted can inhibit the growth of bacteria A. salmonicida and to know the toxicity of Rhizophora sp. stem skin extract against gold fish, the LD50 test was conducted by immersion for 24 hours. Sensitivity test is using the method of Kirby bauer disk blank 6 mm disc with dose used were 10000 ppm, 9000 ppm, 8000 ppm, 7000 ppm, 6000 ppm, 5000 ppm, 4000 ppm, 3000 ppm, 2000 ppm, 1000 ppm and control Ampicilin. The result shown that the Rhizophora sp. stem skin extract can inhibit the growth of bacteria A. salmonicida that in the dose of 1000 ppm with 7,90 mm clear zone . MIC test showed this resueld is 800 ppm has a number of colonies of bacteria aqual 219.66 x 108 CFU/mL. Is able to inhibit the growth of bacteria A. salmonicida. Dose LD50 stem skin extract Rhizophora sp. against gold fish by immersion for 24 hours in 750 ppm.Keyword: Rhizophora sp., Sensitivity, Minimum Inhibitory Concentration, Aeromonas salmonicida